AML1 protein interacts with influenza A virus neuraminidase and upregulates IFN‐β response in infected mammalian cells. (1st April 2020) - Gaur, P.; Kumar, P.; Sharma, A.; Lal, S.K.
Abstract: Neuraminidase (NA) is an integral membrane protein of influenza A virus (IAV) and primarily aids in the release of progeny virions, following the intracellular viral replication cycle. In an attempt to discover new functions of NA, we conducted a classical yeast two‐hybrid screen and found acute myeloid leukaemia marker 1 (AML1) as a novel interacting partner of IAV‐NA. The interaction was further validated by co‐immunoprecipitation in IAV‐infected cells and in an in vitro coupled transcription/translation system. Interestingly, we found an increase in the expression of AML1 upon IAV infection in a dose‐dependent manner. As expected, we also observed an increase in the IFN‐β levels, the first line of defence against viral infections. Subsequently, when AML1 was downregulated using siRNA, the IFN‐β levels were found to be remarkably reduced. Our study also shows that AML1 is induced upon IAV infection and results in the induction of IFN‐β. Thus, AML1 is proposed to be an important player in IFN induction and has a role in an antiviral response against IAV infection. Significance and Impact of the Study: Influenza epidemics and pandemics are constant threats to human health. Development of antiviral therapeutics has focused on important and major IAV proteins as targets. However, the rate at which this virus mutates makes the task challenging. Thus, next‐generation approaches aim at host cellular proteins that aid the virus in its replication. This study reports a new host–virus interaction, of acute myeloid leukaemia marker 1 (AML1) with influenza A neuraminidase (IAV‐NA). We have found that this interaction has a direct effect on the upregulation of host IFN‐β response. Further studies may lead to a greater understanding of this new innate defence pathway in infected cells.